Determinants of the factors affecting the governance structure choice of the pineapple value chain: A case study on market-based agroforestry in Bangladesh - Bapon Mankhin; Mst Esmat Ara Begum; Mohammad Shamsul Hoq; Mohammad Ismail Hossain (Heliyon)
This study examines the governance structures selected by pineapple farmers in the agroforestry system of Bangladesh and the determinants that impact their choices for these structures. To evaluate the factors influencing farmers' decisions to participate in spot markets, bilateral agreements, or association transactions, the study utilizes both quantitative and qualitative approaches, including surveys of 200 farmers, 15 focus group discussions (FGDs), and 2 key informant interviews (KIIs). In order to choose individual participants, the study employed a stratified random sampling technique. Utilising a multivariate probit (MVP) model, the study reveals crucial factors like age, education, farming experience, farm size, market certainty, weather influence, market connection, and pre-delivery conditions. Analysis indicates that spot market is the most favored governance structure (GS) among the three options in the agroforestry system, followed by bilateral transactions and association agreements. Evidence suggests that younger and less educated farmers tend to favor associations, whereas more experienced farmers tend to favor bilateral partnerships. Farms of bigger size typically refrain from joining groups, and unfavorable weather circumstances decrease the probability of engaging in spot markets. The study also demonstrates that robust market links exert an impact on the selection of governance frameworks. Considering the results, the study suggests enhancing training programs to facilitate farmers' understanding and involvement in associations, motivating farmer associations to appeal to larger farms and small farmers, and enhancing market information systems to establish robust market connections.